Transmission Mechanisms of Monetary Policy in Armenia : Evidence from VAR Analysis - Dabla-Norris, Era (IMF Working Papers; Working Paper, 2006)
This paper examines monetary policy transmission in Armenia in light of the authorities' intention to shift to an inflation-targeting regime over the medium term. We find that the capability of monetary policy to influence economic activity and inflation is still limited, as important channels of monetary transmission are not fully functional. In particular, the interest rate channel remains weak, even though there is some evidence of transmission to prices of changes in the repo rate, the central bank's new operating target for inflation. As in other emerging and transition economies with a high degree of dollarization, the exchange rate channel has a strong impact on the inflation rate. Moreover, we find that inflation does respond to broad money shocks, once foreign currency deposits are included.